Migration and Diversity : Human versus Social Capital - Vlad Manole; Maurice Schiff (Institute for the Study of Labor (IZA), 2004)
This paper examines the welfare implications associated with different degrees of diversity or similarity between migrants and natives under both migration and trade. We use a general equilibrium model of migration, human capital and social capital and find that there are three equilibrium solutions: an internal one with half the population of each country migrating to the other country, and two corner solutions where everyone ends up in one of the two countries. The internal solution is unstable and is unlikely to be reached under different levels of human capital across the two countries. The corner solutions are stable and will be reached under most circumstances. If there are human capital differences across the two populations, everyone ends up in the country with the highest initial level of human capital. Welfare under any of the equilibrium solutions rises with the diversity in human capital and decreases with the diversity in social capital between migrants and natives. Trade and both migration solutions reduce inequality between the populations of the two countries by the same amount. In addition, trade and migration are not equivalent if social capital is present: the highest welfare is obtained with migration under the corner solution, the second highest welfare is obtained with trade, and the lowest welfare is obtained with migration under the internal solution. The first two solutions (third solution) raise (may raise or reduce) welfare relative to the no-migration case.
Keywords: F22; F16; F11; J61; 330; migration; trade; social capital; human capital; welfare; Internationale Wanderung; Aussenwirtschaft; Allgemeines Gleichgewicht; Humankapital; Social Capital; Wohlfahrtseffekt; Theorie